Water-based anti-corrosion heat-insulating paint and preparation method thereof
By preparing porous magnesium oxide fillers and cross-linked modified water-based paint bases, the limitations of water-based paint in anti-corrosion and thermal insulation performance are solved, efficient corrosion and thermal insulation effects are achieved, and environmentally friendly and cost-effective advantages are achieved.
Patent Information
- Application Number
- CN202510017310.2
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2025-01-06
- Publication Date
- 2025-02-28
- Estimated Expiration
- 2045-01-06
AI Technical Summary
Water-based paint has limitations in its anti-corrosion and thermal insulation properties. The water resistance and corrosion resistance of film-forming substances are weak, making it difficult to form an effective thermal insulation layer. Drying of moisture may cause water absorption, expansion or corrosion of the substrate.
By preparing porous magnesium oxide fillers with high corrosion resistance and heat insulation properties, and cross-linking and modification of organic cross-linked methyl MQ silicone resin and aqueous acrylic emulsion, a stable water-based paint system was formed.
It significantly improves the anti-corrosion and thermal insulation performance of water-based paint, enhances the durability and adhesion of the coating, reduces thermal conductivity, and has low material cost, which has environmental advantages.
Smart Images

Figure CN119529613A_ABST
Abstract
Description
Technical Field
[0001] The invention belongs to the technical field of coatings, and particularly relates to a water-based anticorrosive heat-insulating paint and a preparation method thereof. Background Art
[0002] Although water-based paint has the advantages of environmental protection, low volatile organic compound (VOC) emissions and good construction performance, it still has certain limitations in terms of anti-corrosion and heat insulation performance.
[0003] First, the film-forming substance of water-based paint is usually an emulsion polymer, which has relatively weak water resistance and corrosion resistance and is easily corroded by moisture and chemical media, resulting in coating failure. Secondly, the film thickness of water-based paint is relatively thin, making it difficult to form an effective thermal insulation layer, thus limiting the thermal insulation effect in high temperature environments. In addition, the moisture in water-based paint may cause water absorption, expansion or corrosion of the substrate during the drying process, especially in a humid environment, which will further affect the adhesion and durability of the coating.
[0004] The Chinese patent document with the authorization announcement number CN115710456B and the name of a water-based functional coating and a preparation method thereof discloses a water-based functional coating and a preparation method thereof, which is composed of a water-based primer and a water-based topcoat, wherein the volume ratio of the water-based primer and the water-based topcoat is 1:1; the water-based primer is composed of an epoxy resin and a primer additive; the percentages of the total weight of the water-based primer are: 50% to 70% of the epoxy resin and 30% to 40% of the primer additive; the water-based topcoat is composed of acrylic polyurethane, modified silica aerogel microspheres, halloysite nanotubes and topcoat additives; the percentages of the total weight of the water-based topcoat are The composition is as follows: 0.5%~1.5% silica aerogel microspheres, 0.5%~12% polar modifier, 0.5%~1.5% halloysite nanotubes, 50%~60% acrylic polyurethane, 10%~15% topcoat curing agent, 15%~18% diluent, and 0.5%~1.5% other additives; after the water-based functional coating prepared by the above technical scheme is cured at room temperature, the 200-micron-thick coating formed can reach a thermal conductivity of less than 2W / (m·K), and its salt spray resistance and electrochemical resistance are good, which is very suitable for long-term use in marine environments, and has excellent heat insulation, vibration reduction and long-term anti-corrosion properties. However, this double-layer painting system may have some functional defects. First of all, the need to apply primer and topcoat separately increases the complexity and time cost of construction, and also increases the risk of stratification, especially when the coatings are not fully cured or the interface adhesion is insufficient. Secondly, in order to achieve the desired performance, too many components need to be added, which will also cause phase separation problems, affect the physical properties of the material, and increase the material cost.
[0005] Therefore, it is necessary to provide a water-based anti-corrosion and thermal insulation paint and a preparation method thereof to solve the problems existing in the above-mentioned prior art. Summary of the invention
[0006] In view of this, the present invention provides a water-based anti-corrosion and heat-insulating paint and a preparation method thereof, which effectively improves the anti-corrosion and heat-insulating properties of the water-based paint by preparing a filler with high anti-corrosion and heat-insulating properties and adopts an organic cross-linking method, and has good overall compatibility.
[0007] To achieve the above object, the present invention provides a method for preparing a water-based anticorrosive thermal insulation paint, comprising the following steps: S1. After heat treatment of corn starch, uniformly mix it with magnesium nitrate hexahydrate and water, cool, age, dry and calcine to obtain an anticorrosive and heat-insulating filler containing porous magnesium oxide; S2, surface treating the methyl MQ silicone resin with sodium dodecyl sulfate and N-ethyl p-toluenesulfonamide to obtain a pretreated methyl MQ silicone resin solution; After N-hydroxytyrosol, N-ethyl p-toluenesulfonamide and water-based acrylic emulsion are mixed evenly, the pre-treated methyl MQ silicone resin solution is added and mixed evenly to obtain a water-based paint base; S3. Evenly mix water, other additives, the anticorrosion and heat-insulating filler prepared in step S1, and the water-based paint base material prepared in step S2 to obtain a water-based anticorrosion and heat-insulating paint.
[0008] The present invention functionally modifies the filler and base material of water-based paint to obtain anticorrosion and heat-insulating fillers and water-based paint base materials, and prepares water-based anticorrosion and heat-insulating paint with excellent anticorrosion and heat-insulating properties under the action of other additives. The preparation of the anticorrosion and heat-insulating filler uses corn starch and magnesium nitrate hexahydrate for heat treatment and high-temperature calcination to construct porous magnesium oxide with excellent chemical resistance and low thermal conductivity. The preparation of the base material uses a hydrophobic methyl MQ silicone resin with a unique stable structure and a hydrophilic water-based acrylic emulsion for cross-linking modification, and forms a stable system under the action of sodium dodecyl sulfate, N-ethyl p-toluenesulfonamide and N-hydroxytyrosol.
[0009] The present invention prepares porous magnesium oxide as an anticorrosive and heat-insulating filler for water-based paint. First, the surface of corn starch particles contains many active groups, such as hydroxyl groups, so that the particle surface is negatively charged. During the soaking process, the ionized Mg 2+ The Mg and hydroxyl groups are adsorbed on the surface of corn starch particles under the action of electrostatic effect and coordination bond. 2+A hydrolysis reaction occurs to produce solid magnesium nitrate and crystallize on the surface of corn starch. After high-temperature calcination, the crystal nucleus of magnesium nitrate gradually increases and decomposes to produce magnesium oxide. At the same time, corn starch particles decompose as embedded templates to produce CO2 to form a macroporous structure. The porous structure helps to increase the specific surface area of magnesium oxide, thereby reducing the heat transfer path and improving the thermal insulation effect; and the air or other gases in the pores have good thermal insulation properties, which can effectively prevent the conduction of heat, help reduce thermal conductivity, and improve thermal insulation performance. Secondly, magnesium oxide has high stability in the air and is not easy to react with moisture or other chemicals. Therefore, it can effectively protect the coating from erosion by moisture, acidic substances or corrosive gases in the external environment.
[0010] In order to further improve the anticorrosion and heat insulation performance of water-based paint and the compatibility between each component, the present invention also prepares a base material with excellent anticorrosion performance and curing speed. First, sodium lauryl sulfate and N-ethyl toluene sulfonamide are used to improve the dispersibility of methyl MQ silicone resin in water, and the sulfonic acid group and amide group are introduced to interact with the methyl MQ silicone resin, giving the methyl MQ silicone resin a certain hydrophilicity. In addition, sodium lauryl sulfate can interact with the resin molecule through its hydrophobic alkyl chain in aqueous solution as a surfactant, helping the resin to be dispersed in water, and then more conducive to increasing its compatibility with aqueous acrylic emulsion. Secondly, N-hydroxytyrosol can form hydrogen bonds with the carboxyl group in the aqueous acrylic emulsion, enhance the stability of the emulsion, and improve the compatibility between the components of the water-based paint through surface hydrogen bonding with the polar groups in the pre-treated methyl MQ silicone resin solution and N-ethyl toluene sulfonamide, thereby forming a stable water-based paint system. In addition, the thermal stability and chemical resistance of the methyl MQ silicone resin itself also further improve the overall anticorrosion effect. At the same time, hydrophilic, hydrophobic interactions and hydrogen bonding also help to form a cross-linked structure, increase the overall cross-linking density, and further accelerate the curing speed of water-based paint.
[0011] In summary, the present invention effectively improves the anti-corrosion and heat-insulating properties of water-based paint through the construction and organic cross-linking modification of porous magnesium oxide, while also demonstrating its unique advantages in cost control and environmental protection, meeting the requirements of environmental protection and cost-effectiveness.
[0012] Optionally, in step S1, corn starch is washed with anhydrous ethanol and heat-treated to obtain heat-treated corn starch, and then magnesium nitrate hexahydrate is dispersed in deionized water, and then the heat-treated corn starch is added, mixed evenly, heated and stirred until it is in a sol state, cooled, aged, and dried to obtain a gel-like solid, and finally calcined under vacuum, and taken out after natural cooling to obtain an anti-corrosion and heat-insulating filler containing porous magnesium oxide.
[0013] In the preparation process of the anticorrosive and heat-insulating filler of the present invention, corn starch is firstly washed with anhydrous ethanol to effectively remove protein and fat in the corn starch, and then dried at 60°C, which helps to effectively remove moisture without destroying the structure of the corn starch, thereby obtaining pure corn starch.
[0014] Optionally, the heat treatment temperature is 50~60℃, the rotation speed is 400~500r / min, and the time is 2~3h; the mass ratio of the corn starch and magnesium nitrate hexahydrate after the heat treatment is 2:1; the heating and stirring temperature is 80~90℃, the rotation speed is 300~400r / min, and the time is 2~3h; the aging time is 24~36h; the drying temperature is 110~120℃, and the time is 12~20h; the calcination temperature is 950~1050℃, and the time is 2~3h; the natural cooling temperature is 70~80℃.
[0015] The present invention uses a mass fraction ratio of 2:1 between heat-treated corn starch and magnesium nitrate hexahydrate, which has a better effect on porous magnesium oxide formed after dispersion of gel. When the ratio of heat-treated corn starch to magnesium nitrate hexahydrate is higher or lower, the size and density of the formed pore structure will be affected.
[0016] Optionally, in step S2, sodium dodecyl sulfate, N-ethyl toluenesulfonamide and methyl MQ silicone resin are dispersed in deionized water to obtain a pretreated methyl MQ silicone resin solution, and then N-hydroxytyrosol is dispersed in deionized water, an aqueous acrylic emulsion is added, and the mixture is stirred evenly, and N-ethyl toluenesulfonamide is added and mixed evenly to obtain a pretreated aqueous acrylic emulsion, and then the pretreated methyl MQ silicone resin solution is added and mixed evenly to obtain a water-based paint base.
[0017] The present invention adds N-ethyl toluene sulfonamide and sodium lauryl sulfate simultaneously when processing methyl MQ silicone resin, mainly because N-ethyl toluene sulfonamide and sodium lauryl sulfate play a joint role in this process, help to improve the dispersibility of silicone resin in water, and produce a good crosslinking effect. When processing water-based acrylic emulsion, N-hydroxytyrosol needs to be added first and then N-ethyl toluene sulfonamide, mainly because N-hydroxytyrosol can be used as an initiator to promote the start of crosslinking reaction, and then N-ethyl toluene sulfonamide is added to further improve crosslinking efficiency and system performance. This order helps to ensure the uniformity and effect of the reaction, thereby optimizing the properties of the material.
[0018] Optionally, the speed of dispersing, mixing and stirring is 400-600 r / min, and the time is 1-2 h; the mass ratio of the sodium dodecyl sulfate, N-ethyl toluenesulfonamide and methyl MQ silicone resin is 1:1:5; the mass ratio of N-hydroxytyrosol, N-ethyl toluenesulfonamide and aqueous acrylic emulsion is 1:1:62.
[0019] Optionally, other additives in S3 are wetting agent LCN407, defoaming agent 204, dispersant NNO and film-forming aid; the film-forming aid is dipropylene glycol butyl ether.
[0020] Optionally, in step S3, deionized water, wetting agent LCN407, dispersant NNO, defoaming agent 204 and the water-based paint base prepared by S2 are stirred evenly, the anti-corrosion and heat-insulating filler prepared by S1 is added and stirred evenly, a film-forming aid is added during stirring, and the material is filtered to obtain a water-based anti-corrosion and heat-insulating paint.
[0021] The order of the filler and base material in the steps of the present invention is to optimize the mixing and dispersion effect. The base material is mixed with the wetting agent, dispersant and defoamer to help create a uniform medium, reduce bubbles and improve wettability, and then the filler is added to better avoid filler aggregation and ensure its uniform distribution, thereby improving the performance and stability of the paint. The addition of the film-forming aid during stirring can ensure that it fully reacts with other ingredients, thereby improving the quality of film formation, and the final filtration can remove undispersed particles to ensure the uniformity and performance of the paint.
[0022] Optionally, the mass ratio of the anti-corrosion and heat-insulating filler prepared by S1 to the water-based paint base prepared by S2 is (5~15):(65~75); the stirring speed of the water-based paint base and other additives is 500~600r / min, and the time is 3~5h; the stirring speed when adding the anti-corrosion and heat-insulating filler prepared by S1 is 500~600r / min, and the time is 7~9h.
[0023] In order to achieve the above-mentioned purpose, the present invention also provides a water-based anti-corrosion and heat-insulating paint prepared by the preparation method of the above-mentioned water-based anti-corrosion and heat-insulating paint, comprising the following raw materials in parts by weight: 20 parts of deionized water, 3 to 5 parts of other additives, 30 to 46 parts of heat-treated corn starch, 15 to 23 parts of magnesium nitrate hexahydrate, 0.5 parts of sodium dodecyl sulfate, 1 part of N-ethyl p-toluenesulfonamide, 2 to 4 parts of methyl MQ silicone resin, 0.5 parts of N-hydroxytyrosol, and 25 to 31 parts of water-based acrylic emulsion.
[0024] Optionally, the other additives include 0.3 parts of wetting agent LCN407, 0.4 parts of dispersant NNO, 0.3 parts of defoaming agent 204 and 2-4 parts of dipropylene glycol butyl ether.
[0025] The water-based anticorrosion and heat-insulating paint obtained by the invention can improve the anticorrosion and heat-insulating performance while also improving the rapid curing property and durability of the water-based paint.
[0026] The above technical solution of the present invention includes at least the following beneficial effects: 1. The present invention uses corn starch as a template, mixes it with magnesium nitrate hexahydrate under mild conditions, and then undergoes heat treatment and high-temperature calcination to form porous magnesium oxide with high corrosion resistance and low thermal conductivity, and the preparation process is simple. The control of the subsequent calcination cooling temperature allows a certain number of hydroxyl groups to form on the surface of the product, which helps to enhance the compatibility and reactivity with the polymer matrix and reduce the amount of filler added.
[0027] 2. The present invention also uses hydrophobic methyl MQ silicone resin and hydrophilic aqueous acrylic emulsion for cross-linking modification, and adds two food-grade additives, N-hydroxytyrosol and N-ethyl p-toluenesulfonamide, as auxiliary agents, which helps to significantly improve the compatibility and cross-linking density between the components and accelerate the curing process of the water-based paint.
[0028] 3. The corn starch, magnesium nitrate hexahydrate, methyl MQ silicone resin, N-hydroxytyrosol, N-ethyl p-toluenesulfonamide and aqueous acrylic emulsion used in the present invention are all non-toxic and harmless materials, and have certain environmental friendliness. The preparation process is streamlined, which helps to reduce the generation of chemical components and pollutants. At the same time, the cost of the materials used in the present invention is low, which helps to improve the cost and environmental advantages of the system, so that it has higher economy and stability in coating applications. BRIEF DESCRIPTION OF THE DRAWINGS
[0029] Figure 1 and Figure 2 The SEM image of the prepared porous magnesium oxide. DETAILED DESCRIPTION
[0030] In order to make the purpose, technical solution and advantages of the embodiment of the present invention clearer, the technical solution of the embodiment of the present invention will be clearly and completely described in combination with the embodiment of the present invention. Obviously, the described embodiment is a part of the embodiment of the present invention, not all the embodiments. Based on the described embodiment of the present invention, all other embodiments obtained by ordinary technicians in this field belong to the scope of protection of the present invention.
[0031] The wetting agent LCN407 used in the following examples was purchased from Guangdong Wengjiang Chemical Reagent Co., Ltd.; the dispersant NNO was purchased from Shanghai McLean Biochemical Co., Ltd.; the defoaming agent 204 was purchased from Shanghai Aladdin Biochemical Technology Co., Ltd.; and the film-forming aid dipropylene glycol butyl ether was purchased from Shanghai McLean Biochemical Co., Ltd.
[0032] Example 1 Preparation of anti-corrosion and heat-insulating filler: Corn starch was washed twice with anhydrous ethanol and dried at 60°C to obtain pretreated corn starch. 15 parts of magnesium nitrate hexahydrate were added to 450 parts of deionized water and dispersed at a speed of 500r / min for 2h, and then 30 parts of pretreated corn starch were added twice and stirred at a speed of 400r / min for 3h to obtain a suspension. The suspension was reacted at 90°C and 400r / min for 2h, cooled to room temperature, aged for 24h, and dried at 120°C for 12h to obtain a gel-like solid. The gel-like solid was calcined at 1050°C for 2h in a tubular furnace under vacuum, and after it was naturally cooled to 80°C, a porous magnesium oxide anti-corrosion and heat-insulating filler was obtained.
[0033] Preparation of water-based paint base: 0.5 parts of sodium dodecyl sulfate, 0.5 parts of N-ethyl p-toluenesulfonamide and 2 parts of methyl MQ silicone resin are added to 10 parts of deionized water, and dispersed at a speed of 600 r / min for 1 hour to obtain a pre-treated methyl MQ silicone resin solution. 0.5 parts of N-hydroxytyrosol are added to 50 parts of deionized water, dispersed at a speed of 600 r / min for 1 hour, 25 parts of water-based acrylic emulsion are added, stirred at a speed of 600 r / min for 1 hour, 0.5 parts of N-ethyl p-toluenesulfonamide are added, stirred at a speed of 600 r / min for 1 hour, and then the pre-treated methyl MQ silicone resin solution is added, and stirred at a speed of 600 r / min for 1 hour to obtain a water-based paint base.
[0034] Preparation of water-based anti-corrosion and thermal insulation paint: 75 parts of base material, 0.3 parts of wetting agent LCN407, 0.4 parts of dispersant NNO, 0.3 parts of defoaming agent 204 and 20 parts of deionized water are stirred at a speed of 600 r / min for 3 hours, 5 parts of anti-corrosion and thermal insulation filler are added, and the mixture is stirred at a speed of 500 r / min for 7 hours. During the stirring period, 2 parts of film-forming aid are added, and the material is filtered to obtain a water-based anti-corrosion and thermal insulation paint.
[0035] Example 2 Preparation of anti-corrosion and heat-insulating filler: Corn starch was washed with anhydrous ethanol for 3 times and dried at 60°C to obtain pretreated corn starch. 15 parts of magnesium nitrate hexahydrate were added to 450 parts of deionized water and dispersed at a speed of 500r / min for 2h, and then 30 parts of pretreated corn starch were added in 2 times and stirred at a speed of 400r / min for 3h to obtain a suspension. The suspension was reacted at 90°C and 400r / min for 2h, cooled to room temperature, aged for 24h, and dried at 120°C for 12h to obtain a gel-like solid. The gel-like solid was calcined at 1050°C for 2h in a tubular furnace under vacuum, and after it was naturally cooled to 80°C, a porous magnesium oxide anti-corrosion and heat-insulating filler was obtained.
[0036] Preparation of water-based paint base: 0.5 parts of sodium dodecyl sulfate, 0.5 parts of N-ethyl p-toluenesulfonamide and 2.5 parts of methyl MQ silicone resin are added to 10 parts of deionized water, and dispersed at a speed of 400 r / min for 2 hours to obtain a pre-treated methyl MQ silicone resin solution. 0.5 parts of N-hydroxytyrosol are added to 50 parts of deionized water, dispersed at a speed of 400 r / min for 2 hours, 31 parts of water-based acrylic emulsion are added, stirred at a speed of 400 r / min for 2 hours, 0.5 parts of N-ethyl p-toluenesulfonamide are added, stirred at a speed of 400 r / min for 2 hours, and then the pre-treated methyl MQ silicone resin solution is added, and stirred at a speed of 400 r / min for 2 hours to obtain a water-based paint base.
[0037] Preparation of water-based anti-corrosion and thermal insulation paint: 73 parts of base material, 0.3 parts of wetting agent LCN407, 0.4 parts of dispersant NNO, 0.3 parts of defoaming agent 204 and 20 parts of deionized water are stirred at a speed of 600 r / min for 3 hours, 7 parts of anti-corrosion and thermal insulation filler are added, and the mixture is stirred at a speed of 600 r / min for 8 hours. During the stirring period, 3 parts of film-forming aid are added, and the material is filtered to obtain a water-based anti-corrosion and thermal insulation paint.
[0038] Example 3 Preparation of anti-corrosion and heat-insulating filler: Corn starch was washed twice with anhydrous ethanol and dried at 60°C to obtain pretreated corn starch. 15 parts of magnesium nitrate hexahydrate were added to 450 parts of deionized water and dispersed at a speed of 500r / min for 2h, and then 30 parts of pretreated corn starch were added twice and stirred at a speed of 400r / min for 3h to obtain a suspension. The suspension was reacted at 90°C and 400r / min for 2h, cooled to room temperature, aged for 24h, and dried at 120°C for 12h to obtain a gel-like solid. The gel-like solid was calcined at 1050°C for 2h in a tubular furnace under vacuum, and after it was naturally cooled to 80°C, a porous magnesium oxide anti-corrosion and heat-insulating filler was obtained.
[0039] Preparation of water-based paint base: 0.5 parts of sodium dodecyl sulfate, 0.5 parts of N-ethyl p-toluenesulfonamide and 2.5 parts of methyl MQ silicone resin are added to 10 parts of deionized water, and dispersed at a speed of 400 r / min for 2 hours to obtain a pre-treated methyl MQ silicone resin solution. 0.5 parts of N-hydroxytyrosol are added to 50 parts of deionized water, dispersed at a speed of 400 r / min for 2 hours, 31 parts of water-based acrylic emulsion are added, stirred at a speed of 400 r / min for 2 hours, 0.5 parts of N-ethyl p-toluenesulfonamide are added, stirred at a speed of 400 r / min for 2 hours, and then the pre-treated methyl MQ silicone resin solution is added, and stirred at a speed of 400 r / min for 2 hours to obtain a water-based paint base.
[0040] Preparation of water-based anti-corrosion and thermal insulation paint: 72 parts of base material, 0.3 parts of wetting agent LCN407, 0.4 parts of dispersant NNO, 0.3 parts of defoaming agent 204 and 20 parts of deionized water are stirred at a speed of 500 r / min for 3.5 hours, 8 parts of anti-corrosion and thermal insulation filler are added, and stirred at a speed of 500 r / min for 8 hours. During the stirring period, 2 parts of film-forming aid are added, and the material is filtered to obtain a water-based anti-corrosion and thermal insulation paint.
[0041] Example 4 Preparation of anti-corrosion and heat-insulating filler: Corn starch was washed with anhydrous ethanol for 3 times and dried at 60°C to obtain pretreated corn starch. 15 parts of magnesium nitrate hexahydrate were added to 450 parts of deionized water and dispersed at a speed of 500r / min for 2h, and then 30 parts of pretreated corn starch were added in 2 times and stirred at a speed of 400r / min for 3h to obtain a suspension. The suspension was reacted at 90°C and 400r / min for 2h, cooled to room temperature, aged for 24h, and dried at 120°C for 12h to obtain a gel-like solid. The gel-like solid was calcined at 1050°C for 2h in a tubular furnace under vacuum, and after it was naturally cooled to 80°C, a porous magnesium oxide anti-corrosion and heat-insulating filler was obtained.
[0042] Preparation of water-based paint base: 0.5 parts of sodium dodecyl sulfate, 0.5 parts of N-ethyl p-toluenesulfonamide and 2.5 parts of methyl MQ silicone resin are added to 10 parts of deionized water, and dispersed at a speed of 400 r / min for 2 hours to obtain a pre-treated methyl MQ silicone resin solution. 0.5 parts of N-hydroxytyrosol are added to 50 parts of deionized water, dispersed at a speed of 400 r / min for 2 hours, 31 parts of water-based acrylic emulsion are added, stirred at a speed of 400 r / min for 2 hours, 0.5 parts of N-ethyl p-toluenesulfonamide are added, stirred at a speed of 400 r / min for 2 hours, and then the pre-treated methyl MQ silicone resin solution is added, and stirred at a speed of 400 r / min for 2 hours to obtain a water-based paint base.
[0043] Preparation of water-based anti-corrosion and thermal insulation paint: 70 parts of base material, 0.3 parts of wetting agent LCN407, 0.4 parts of dispersant NNO, 0.3 parts of defoaming agent 204 and 20 parts of deionized water are stirred at a speed of 600 r / min for 4 hours, 10 parts of anti-corrosion and thermal insulation filler are added, and the mixture is stirred at a speed of 600 r / min for 8 hours. During the stirring period, 4 parts of film-forming aid are added, and the material is filtered to obtain a water-based anti-corrosion and thermal insulation paint.
[0044] Example 5 Preparation of thermal insulation and anti-corrosion filler: Corn starch was washed with anhydrous ethanol for 3 times and dried at 60°C to obtain pretreated corn starch. 23 parts of magnesium nitrate hexahydrate were added to 700 parts of deionized water and dispersed at a speed of 400r / min for 3 hours, and then 46 parts of pretreated corn starch were added in 3 times and stirred at a speed of 400r / min for 4 hours to obtain a suspension. The suspension was reacted at 80°C and 300r / min for 3 hours, cooled to room temperature, aged for 36 hours, and dried at 110°C for 20 hours to obtain a gel-like solid. The gel-like solid was calcined at 950°C for 3 hours in a tubular furnace under vacuum, and after it was naturally cooled to 70°C, a porous magnesium oxide anti-corrosion and thermal insulation filler was obtained.
[0045] Preparation of water-based paint base: 0.5 parts of sodium dodecyl sulfate, 0.5 parts of N-ethyl p-toluenesulfonamide and 2.5 parts of methyl MQ silicone resin are added to 10 parts of deionized water, and dispersed at a speed of 400 r / min for 2 hours to obtain a pre-treated methyl MQ silicone resin solution. 0.5 parts of N-hydroxytyrosol are added to 50 parts of deionized water, dispersed at a speed of 400 r / min for 2 hours, 31 parts of water-based acrylic emulsion are added, stirred at a speed of 400 r / min for 2 hours, 0.5 parts of N-ethyl p-toluenesulfonamide are added, stirred at a speed of 400 r / min for 2 hours, and then the pre-treated methyl MQ silicone resin solution is added, and stirred at a speed of 400 r / min for 2 hours to obtain a water-based paint base.
[0046] Preparation of water-based anti-corrosion and thermal insulation paint: 68 parts of base material, 0.3 parts of wetting agent LCN407, 0.4 parts of dispersant NNO, 0.3 parts of defoaming agent 204 and 20 parts of deionized water are stirred at a speed of 600 r / min for 3 hours, 12 parts of anti-corrosion and thermal insulation filler are added, and the mixture is stirred at a speed of 600 r / min for 7 hours. During the stirring period, 2 parts of film-forming aid are added, and the material is filtered to obtain a water-based anti-corrosion and thermal insulation paint.
[0047] Example 6 Preparation of thermal insulation and anti-corrosion filler: Corn starch was washed with anhydrous ethanol for 3 times and dried at 60°C to obtain pretreated corn starch. 23 parts of magnesium nitrate hexahydrate were added to 700 parts of deionized water and dispersed at a speed of 400r / min for 3 hours, and then 46 parts of pretreated corn starch were added in 3 times and stirred at a speed of 400r / min for 4 hours to obtain a suspension. The suspension was reacted at 80°C and 300r / min for 3 hours, cooled to room temperature, aged for 36 hours, and dried at 110°C for 20 hours to obtain a gel-like solid. The gel-like solid was calcined at 950°C for 3 hours in a tubular furnace under vacuum, and after it was naturally cooled to 70°C, a porous magnesium oxide anti-corrosion and thermal insulation filler was obtained.
[0048] Preparation of water-based paint base: 0.5 parts of sodium dodecyl sulfate, 0.5 parts of N-ethyl p-toluenesulfonamide and 4 parts of methyl MQ silicone resin are added to 10 parts of deionized water, and dispersed at a speed of 400 r / min for 2 hours to obtain a pre-treated methyl MQ silicone resin solution. 0.5 parts of N-hydroxytyrosol are added to 50 parts of deionized water, dispersed at a speed of 400 r / min for 2 hours, 31 parts of water-based acrylic emulsion are added, stirred at a speed of 400 r / min for 2 hours, 0.5 parts of N-ethyl p-toluenesulfonamide are added, stirred at a speed of 400 r / min for 2 hours, and then the pre-treated methyl MQ silicone resin solution is added, and stirred at a speed of 400 r / min for 2 hours to obtain a water-based paint base.
[0049] Preparation of water-based anti-corrosion and thermal insulation paint: 65 parts of base material, 0.3 parts of wetting agent LCN407, 0.4 parts of dispersant NNO, 0.3 parts of defoaming agent 204 and 20 parts of deionized water are stirred at a speed of 500 r / min for 5 hours, 15 parts of anti-corrosion and thermal insulation filler are added, and stirred at a speed of 500 r / min for 9 hours. During the stirring period, 3 parts of film-forming aid are added, and the material is filtered to obtain a water-based anti-corrosion and thermal insulation paint.
[0050] The present invention also provides comparative examples and related tests.
[0051] Comparative Example 1 The difference between Comparative Example 1 and Example 4 is that the anti-corrosion and heat-insulating filler is not the porous magnesium oxide prepared in Example 1, but commercially available spherical magnesium oxide. The other compositions and preparation methods are the same as those in Example 4, and finally a water-based anti-corrosion and heat-insulating paint is prepared.
[0052] Comparative Example 2 The difference between Comparative Example 2 and Example 4 is that 5 parts of methyl MQ silicone resin are not added, and 5 parts of methyl MQ silicone resin are replaced by 5 parts of water-based acrylic emulsion. The other compositions and preparation methods are the same as those of Example 4, and finally a water-based anticorrosive heat-insulating paint is prepared.
[0053] Comparative Example 3 The difference between Comparative Example 3 and Example 4 is that 0.5 parts of N-hydroxytyrosol are not added, and 0.5 parts of N-hydroxytyrosol are replaced by 0.5 parts of N-ethyl-p-toluenesulfonamide. The other compositions and preparation methods are the same as those of Example 4, and finally a water-based anticorrosive heat-insulating paint is prepared.
[0054] Comparative Example 4 The difference between Comparative Example 4 and Example 4 is that 1 part of N-ethyl-p-toluenesulfonamide is not added, and 1 part of N-ethyl-p-toluenesulfonamide is replaced by 1 part of N-hydroxytyrosol. The other compositions and preparation methods are the same as those of Example 4, and finally a water-based anticorrosive heat-insulating paint is prepared.
[0055] The water-based anticorrosion and thermal insulation paints of Examples 1 to 6 and Comparative Examples 1 to 4 were subjected to relevant performance tests according to the test standards and performance indicators in Table 1. The test data are shown in Tables 2 and 3. The porous magnesium oxide prepared in Example 1 was characterized by SEM morphology. The results are shown in Tables 2 and 3. Figure 1 and Figure 2 shown.
[0056] Table 1
[0057] Table 2
[0058] It can be seen from Tables 1 and 2 that the corrosion resistance, durability and curing speed of the water-based anticorrosion and thermal insulation paints prepared in Examples 1 to 6 are significantly higher than those of the water-based anticorrosion and thermal insulation paints prepared in Comparative Examples 1 to 4, and Example 4 has the best performance and is the optimal solution of the present invention.
[0059] Combining the data in Table 1 and Table 2, by comparing Example 4 with Comparative Examples 1 to 4, it can be seen that the test data of Comparative Examples 1 and 2 in Table 2 do not meet the performance indicators of Table 1. It can be seen that the addition of porous magnesium oxide, methyl MQ silicone resin, N-hydroxytyrosol and N-ethyl p-toluenesulfonamide has a certain degree of influence on the corrosion resistance, durability and curing speed of water-based paint.
[0060] According to the test results of impact resistance, water resistance, acid resistance and alkali resistance of comparative examples 1, 2 and embodiment 4, and in conjunction with table 1 performance index, it can be seen that without adding porous magnesium oxide and methyl MQ silicone resin, water-based paint will have cracks and weak deformation under 50cm positive and negative impacts, and bubbling and cracking will occur within 120 hours, and it can be seen that the addition of porous magnesium oxide and methyl MQ silicone resin has a greater impact on the anticorrosive performance of water-based paint. And the anticorrosive performance test data of comparative example 3 basically meets the performance index of table 1, and comparative example 4 also basically meets the performance index of table 1 except impact resistance, and it can be seen that the addition of N-ethyl toluenesulfonamide has less impact on the anticorrosive performance of water-based paint, and the addition of N-hydroxytyrosol has no impact on the anticorrosive performance of water-based paint.
[0061] According to the test results of impact resistance, water resistance, artificial aging resistance, acid resistance and alkali resistance of Comparative Examples 1 to 4 and Example 4, and combined with the performance indicators in Table 1, it can be seen that the test data of Comparative Examples 1 and 2 in Table 2 do not meet the performance indicators in Table 1, Comparative Example 3 basically meets the performance indicators in Table 1 except for artificial aging resistance, and Comparative Example 4 also basically meets the performance indicators in Table 1 except for impact resistance. It can be seen that porous magnesium oxide filler and methyl MQ silicone resin have a greater effect on the durability of water-based paint, while the addition of N-ethyl toluenesulfonamide and N-hydroxytyrosol has less effect on the durability of water-based paint.
[0062] According to the test results of surface drying and actual drying of comparative examples 1 to 4 and embodiment 4, and in combination with the performance indicators in Table 1, it can be seen that the test data of comparative examples 1 to 4 do not meet the performance indicators in Table 1, and the surface drying and actual drying data in comparative example 4 differ the most from the data in embodiment 4, which are 3.0 and 32 hours, which are 2.5 and 12 hours different from the data in embodiment 4; the surface drying and actual drying data in comparative example 3 differ greatly from the data in embodiment 4, which are 2.9 and 33 hours, which are 2.4 and 13 hours different from the data in embodiment 4; it can be seen that the addition of N-hydroxytyrosol and N-ethyl toluenesulfonamide has a greater effect on the curing speed of water-based paint, and the addition of porous magnesium oxide and methyl MQ silicone resin has a relatively small effect on the curing speed of water-based paint.
[0063] Table 3
[0064] It can be seen from Table 1 and Table 3 that the test results of the water-based anti-corrosion and thermal insulation paints prepared in Examples 1 to 6 obviously meet the performance indicators in Table 1, while the solar reflectance, near-infrared reflectance, and hemispherical reflectance of Comparative Examples 1 to 4 do not meet the performance indicators in Table 1, and except for the thermal conductivity of Comparative Example 3 which meets the performance indicators in Table 1, Comparative Examples 1, 2, and 4 do not meet the requirements, that is, the thermal insulation performance of Examples 1 to 6 is significantly higher than that of the water-based anti-corrosion and thermal insulation paints prepared in Comparative Examples 1 to 4, and Example 4 has the best performance, which is the optimal solution of the present invention.
[0065] In combination with the data in Table 1 and Table 3, from the test data of the sunlight reflectance, near-infrared light reflectance, hemispherical reflectivity and thermal conductivity of Example 4 and Comparative Examples 1 to 4, and in combination with the performance indicators in Table 1, it can be seen that the sunlight reflectance, near-infrared light reflectance and hemispherical reflectance of Comparative Examples 1 to 4 do not meet the performance indicators in Table 1, and except that the thermal conductivity of Comparative Example 3 meets the performance indicators in Table 1, Comparative Examples 1, 2 and 4 do not meet the performance indicators. It can be seen that the addition of porous magnesium oxide, methyl MQ silicone resin, N-hydroxytyrosol and N-ethyl toluenesulfonamide all has a certain degree of influence on the thermal insulation performance of water-based paint, and the addition of porous magnesium oxide and methyl MQ silicone resin has a greater influence on the curing speed of water-based paint, and the addition of N-hydroxytyrosol and N-ethyl toluenesulfonamide has a relatively small influence on the curing speed of water-based paint.
[0066] The above are preferred embodiments of the present invention. It should be pointed out that, for ordinary technicians in this technical field, several improvements and modifications can be made without departing from the principles of the present invention. These improvements and modifications should also be regarded as within the scope of protection of the present invention.
Claims
1. A method for preparing a water-based anticorrosive and thermal insulating paint, characterized in that: The following steps are involved: S1. After heat treatment of corn starch, uniformly mix it with magnesium nitrate hexahydrate and water, cool, age, dry and calcine to obtain an anticorrosive and heat-insulating filler containing porous magnesium oxide; S2, surface treating the methyl MQ silicone resin with sodium dodecyl sulfate and N-ethyl p-toluenesulfonamide to obtain a pretreated methyl MQ silicone resin solution; After N-hydroxytyrosol, N-ethyl p-toluenesulfonamide and water-based acrylic emulsion are mixed evenly, the pre-treated methyl MQ silicone resin solution is added and mixed evenly to obtain a water-based paint base; S3. Evenly mix water, other additives, the anticorrosion and heat-insulating filler prepared in step S1, and the water-based paint base material prepared in step S2 to obtain a water-based anticorrosion and heat-insulating paint.
2. The method for preparing a water-based anticorrosive heat-insulating paint according to claim 1, characterized in that: In step S1, corn starch is washed with anhydrous ethanol and heat-treated to obtain heat-treated corn starch, and then magnesium nitrate hexahydrate is dispersed in deionized water, and then the heat-treated corn starch is added, mixed evenly, heated and stirred to a sol state, cooled, aged, and dried to obtain a gel-like solid, and finally calcined under vacuum, and taken out after natural cooling to obtain an anti-corrosion and heat-insulating filler containing porous magnesium oxide.
3. The method for preparing a water-based anticorrosive heat-insulating paint according to claim 2, characterized in that: The heat treatment temperature is 50-60°C, the rotation speed is 400-500r / min, and the time is 2-3h; the mass ratio of the corn starch and magnesium nitrate hexahydrate after the heat treatment is 2:1; the heating and stirring temperature is 90-100°C, the rotation speed is 300-400r / min, and the time is 2-3h; the aging time is 24-36h; the drying temperature is 110-120°C, and the time is 12-20h; the calcination temperature is 950-1050°C, and the time is 2-3h; and the natural cooling temperature is 70-80°C.
4. The method for preparing a water-based anticorrosive heat-insulating paint according to claim 1, characterized in that: In the step S2, sodium dodecyl sulfate, N-ethyl p-toluenesulfonamide and methyl MQ silicone resin are dispersed in deionized water to obtain a pretreated methyl MQ silicone resin solution, and then N-hydroxytyrosol is dispersed in deionized water, an aqueous acrylic emulsion is added, and the mixture is stirred evenly, and N-ethyl p-toluenesulfonamide is added and mixed evenly to obtain a pretreated aqueous acrylic emulsion, and then the pretreated methyl MQ silicone resin solution is added and mixed evenly to obtain a water-based paint base.
5. The method for preparing a water-based anticorrosive heat-insulating paint according to claim 4, characterized in that: The speeds of dispersion, mixing and stirring are all 400-600 r / min, and the time is 1-2 h; the mass ratio of sodium dodecyl sulfate, N-ethyl p-toluenesulfonamide and methyl MQ silicone resin is 1:1:5; the mass ratio of N-hydroxytyrosol, N-ethyl p-toluenesulfonamide and aqueous acrylic emulsion is 1:1:
62.
6. The method for preparing a water-based anticorrosive heat-insulating paint according to claim 1, characterized in that: In the step S3, other additives are wetting agent LCN407, defoaming agent 204, dispersant NNO and film-forming aid; the film-forming aid is dipropylene glycol butyl ether.
7. The method for preparing a water-based anticorrosive heat-insulating paint according to claim 1, characterized in that: In the step S3, deionized water, wetting agent LCN407, dispersant NNO, defoaming agent 204 and the water-based paint base prepared by S2 are stirred evenly, and the anti-corrosion and heat-insulating filler prepared by S1 is added and stirred evenly. During the stirring, a film-forming aid is added, and the material is filtered to obtain a water-based anti-corrosion and heat-insulating paint.
8. The method for preparing a water-based anticorrosive heat-insulating paint according to claim 7, characterized in that: The mass ratio of the anti-corrosion and heat-insulating filler prepared by S1 to the water-based paint base prepared by S2 is (5~15):(65~75); the stirring speed of the water-based paint base and other additives is 500~600r / min, and the time is 3~5h; the stirring speed when adding the anti-corrosion and heat-insulating filler prepared by S1 is 500~600r / min, and the time is 7~9h.
9. A water-based anticorrosion and heat-insulating paint, characterized in that: The paint is prepared by the method for preparing a water-based anticorrosion and thermal insulation paint according to any one of claims 1 to 8, and comprises the following raw materials in parts by weight: 20 parts of deionized water, 3 to 5 parts of other additives, 30 to 46 parts of heat-treated corn starch, 15 to 23 parts of magnesium nitrate hexahydrate, 0.5 parts of sodium dodecyl sulfate, 1 part of N-ethyl p-toluenesulfonamide, 2 to 4 parts of methyl MQ silicone resin, 0.5 parts of N-hydroxytyrosol, and 25 to 31 parts of water-based acrylic emulsion.
10. A water-based anticorrosion and heat-insulating paint according to claim 9, characterized in that: The other additives include 0.3 parts of wetting agent LCN407, 0.4 parts of dispersant NNO, 0.3 parts of defoaming agent 204 and 2-4 parts of dipropylene glycol butyl ether.
Citation Information
Patent Citations
A water-based functional coating and its preparation method
CN115710456B
Antimicrobial anticorrosive paint and preparation method thereof
CN104031442A
Concrete surface protection system
CN104530972A
Waterborne acrylic heat-insulation coating and its preparation method
CN107286782A
Sunlight heat-reflection, heat-insulation and heat-preservation sand-in-water colored environment-friendly coating and preparation method thereof
CN108219562A